Asymmetric syntheses of benzaldehyde and o-anisaldehyde methyl isopropyl acetals - Davies, S; Correia, L (1996)
Asymmetric syntheses of (+)-(αR)-benzaldehyde and (+)-(αR)-o-anisaldehyde methyl isopropyl acetals in 93 and > 95% ee respectively using methodology based on the stereoselective reactions of enantiopure (ortho-substituted benzaldehyde) chromium tricarbonyl complexes are described.